Parametrization of CPW for Photonics Application with the Use of Closed Form Formulas - Kula, Sebastian (Periodica Polytechnica Electrical Engineering and Computer Science, 2020)
In this paper parametrized analysis of CPW (Coplanar Waveguide) applied in photonics is presented. The analysis is based on analytical formulas, which were delivered and modified from conformal mapping technique, and also after review of available literature from analytical models for the conventional CPW. Adjustment of the already reported CPW formulas was performed to properly model thin films CPW structures in PIC (Photonic Integrated Circuit). Thus, a closed expressions were proposed to simulate basic parameters, like: per unit length (p.u.l.) R (resistance), L (inductance), C (capacitance), G (conductance) and propagation quantity like characteristic impedance Zo versus frequency. The CPW line dedicated for the PIC application, is based on InP (Indium Phosphide) substrate and with air or BCB (Benzocyclobutene) surroundings of the metallization on the top. The modified formulas are curve-fitting approximations, with new fitting coefficients. Essential modifications are for p.u.l. C and p.u.l. L. Usefulness and effectiveness of the modified method was verified through results comparison with simulations in full-wave Electronic Design Automation software, with the circuit simulator QUCS and with real measurements, conducted with the use of PNA (Performance Network Analyzer). The paper novelty are new coefficients for analytical formulas, implementation of modified formulas in the octave code and model parametrization for geometrical parameters.